Students' Perceptions of Using Cici AI's Voice Communication Feature in Improving English Speaking Ability - Novi Yanti; Damanik, Emeliya Sukma Dara (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
This study explores students' perceptions of using Cici AI's voice communication feature to improve their English speaking abilities. Using a qualitative approach with a descriptive phenomenological design, data was collected from 25 university students through a questionnaire and involved 5 selected students for in-depth interviews. The results of the study highlighted five main findings, namely: (1) Usefulness; (2) Easiness; (3) Students' Confidence; (4) Speaking Ability Improvement; and (5) Access Difficulties. The findings showed that students gave a positive perception of Cici AI's voice communication feature as a tool to improve their English speaking ability. This research contributes to the growing body of research on AI in language learning on how Cici AI can support students in improving English speaking ability. Future research would be valuable to explore the long-term impact of Cici AI in improving English speaking skills in various educational settings.